THE USE OF ELECTRONIC AND PAPER DOCUMENTS IN THE PERSONNEL MANAGEMENT SYSTEM OF MODERN ORGANIZATIONS - T. Suvalova (Вестник университета)
For the majority of Russian companies in recent years to become a reality the implementation of mixed paper and electronic document management with the constant increase in its electronic component and the emergence of new organizational and technological forms. The idea of mixed electronic and paper document is the basis of the conceptual approach of gradual expansion of the use of electronic documents. This fact is particularly important in view of what is now different organizations are at various stages of implementation and use of electronic document technologies. Furthermore, the use in the foreseeable future a mixed electronic and paper document allows to take into account the advantages and disadvantages of paper and electronic media.